Antibacterial Potency of Prabumulih’s Pineapple Leaves Extract (Ananas comosus) Towards Enterococcus faecalis - Diana Lestari; Rini Bikarindrasari; Trisnawaty K (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2023)
Introduction: Unsuccessful elimination procedures of Gram-positive bacteria (Enterococcus faecalis) often lead to failure of endodontic treatment. It is necessary to use irrigation solutions to eliminate it from the root canal. The leaves of Pineapple (Ananas comosus) that are widely cultivated in Prabumulih have antibacterial properties due to active compounds such as bromelain enzymes, flavonoids, phenols, saponins, tannins, and alkaloids and have potential as an alternative material for root canal irrigation. Purpose: This study aimed to determine the antibacterial potency of Prabumulih pineapple leaf extract (Ananas comosus) against E. faecalis. Methods: This is an in vitro quasi-experimental laboratory study with a post-test-only control group study design. The test group consisted of Prabumulih pineapple leaf extract at concentrations of 1.56%, 3.125%, 6.25%, and 12,5% obtained using the maceration method. The positive control was NaOCl 2.5%, and distilled water was the negative control. The antibacterial activity of the extract using the disc diffusion method for the inhibition zone test, the dilution method for the minimum inhibitory concentration (MIC) test, and solid dilution for the minimum bactericidal concentration (MBC) test. Results: It showed that Prabumulih pineapple leaves extract has antibacterial potency against E. faecalis with the largest average inhibition zone at a concentration of 12.5% (2.324 mm), MIC at a concentration of 12,5%, and MBC also at a concentration of 12,5%. Conclusion: Prabumulih pineapple leaf extract has antibacterial potency against Enterococcus faecalis.